Association of different types of milk with depression and anxiety: a prospective cohort study and Mendelian randomization analysis - Wu, Chunying; Liu, Yusheng; Lai, Yigui; Wang, Qiang; Wu, Siqi; Fan, Huijie; Liu, Yanyan; Zhao, Xiaoshan; Jiang, Xuefeng (Frontiers in Nutrition, 2024)
The relationship between different types of milk and depression and anxiety remains unclear, with limited evidence from prospective cohort studies. This study aims to evaluate this relationship using data from the UK Biobank cohort and to explore its potential causality through Mendelian randomization (MR) analysis.Methods: Cox proportional hazards models were used to assess the association between different milk types and the risk of depression and anxiety among 357,568 UK Biobank participants free of these conditions at baseline. To further explore causality, a 2-sample MR analysis was conducted using data from the FinnGen study.Results: During a median follow-up period of 13.5 years (interquartile range, 12.6 to 14.2 years), among 357,568 participants (mean [SD] age, 56.83 [8.06] years, 171,246 male individuals [47.9%]), a total of 13,065 and 13,339 participants were diagnosed with depression and anxiety, respectively. In the fully adjusted model (adjusted for sociodemographics characteristics, lifestyle behaviors and health indicators), full cream milk was related to a lower risk of anxiety (HR = 0.84, 95% CI: 0.75-0.94). Semi-skimmed milk had a lower risk of depression (HR = 0.88, 95% CI: 0.80-0.96) and anxiety (HR = 0.90, 95% CI: 0.82-0.98). No significant relationships were found between skimmed milk and depression/anxiety. Other types were related to an increased risk of depression (HR = 1.14, 95% CI: 1.02-1.28). After Bonferroni correction, the 2-sample MR analysis revealed a potential protective causal relationship between semi-skimmed milk and depression (OR = 0.83, 95% CI: 0.73-0.95, P = 0.006) and anxiety (OR = 0.71, 95% CI: 0.59-0.85, P < 0.001).These findings indicate that semi-skimmed milk consumption may be linked to a lower risk of depression and anxiety, potentially highlighting its role in dietary strategies to promote mental health.